Aktifitas Stimulan Sistem Saraf Pusat Ekstrak Biji Pinang ( Areca catechu, L ) Terhadap Mencit Putih ( Mus musculus, L) - Suhatri Suhatri; Yimmi Syavardie; Zet Rizal (STIFARM Padang, 2011)
The stimulant activity of central nerve systems of areca seed (Areca cathecu, L.), at white mouse ( Mus musculus, L ) had been done by using method hanging test, evasi test, swim test and discrimination maze. Drug dose given is 0.5 mg/20 gram BW white mouse, 1 mg/20 gram BW white mouse, 2 mg/ 20 gram BW white mouse in oral mechanism. As negative control is applied by Tween 80 2% and condensation of comparator is applied by Caffeine.Activity test result from seed extract Pinang ( Areca cathecu, L. ) to white mouse ( Mus musculus, L. ) the obtained result signifikan ( P < 0.01 ) as stimulant central nerve systems.